Empyema thoracis: a 10-year comparative review of hospitalised children from south Asia. Issue 11 (11th November 2003) - Baranwal, A K; Singh, M; Marwaha, R K; Kumar, L
Abstract : Aims: To study the clinical and microbial profile of childhood empyema in South Asia and to identify the changes over the past three decades. Methods: A total of 265 children (aged 1 month to 12 years) with empyema admitted to the Advanced Pediatric Center, PGIMER, Chandigarh, India in 1989–98, were reviewed retrospectively. Results and Conclusions: One third of children were under 5. Culture positivity had decreased significantly (48% v 75%) over the years. Staphylococcus aureus continues to be the commonest (77%) aetiological agent; clustering was seen during hot and humid months (46%). Culture positive Streptococcus pneumoniae cases also decreased (9% v 27%); all were seen during the winter and spring season. Gram negative rods grew in more patients (11% v 7%). Community acquired methicillin resistant S aureus (MRSA) was isolated in three patients. Most children (93%) were treated with parenteral cloxacillin and an aminoglycoside. Tube drainage (TD) was used in 92% of fibropurulent cases, and was successful in 79%. Of 48 patients with failed TD, 12 needed decortication; limited thoracotomy was sufficient in the remaining 36. Surgery was mainly required by children with persistent pleural sepsis after 10 days of TD. Delaying surgery until 14 days had a significantly higher potential of requiring decortication. Early change to oral antibiotics (after 1–2 weeks of parenteral therapy) reduced the hospital stay significantly (17+7 v 23+7 days) without compromising long term outcome. Twenty two patients presenting late in the chronic stage underwent decortication at admission.